Quality of Life Cervical Cancer Patients Stage IB-IIB After Neoadjuvant Chemotherapy Followed by Surgery Versus Surgery Alone - Arista, Nurkamilawati; Utama Pelupessy, Nugraha; Butje Leonardy, Rudy; Hamid, Firdaus; Arifuddin, Sharvianty; Susiawaty, (International Journal of Psychosocial Rehabilitation, 2020)
Cervical cancer is the leading cause of death after breast cancer. The research aimed to determine the effect of giving adjuvant chemotherapy on quality of life in cervical cancer patients stage IB-IIB. Forty-three cervical cancer patients stage IB-IIB who were established based on history taking, physical examination, biopsy, radiology, laboratory, and clinical staging were included in this study. Platinum-based chemotherapy was performed in three to six series, followed by surgery in group one (24 respondents) and surgery alone in group two (19 respondents). The EORTC QLQ 30 and EORTC CX-24 questionnaires were administered after twenty-one days after surgery. An analysis of the results of the post-chemotherapy laboratory results was also carried out, the results of the operating outcomes, and a comparison of estimated treatment costs. Analytical test results showed levels of leukocytes (p = 0.002) and platelets (p = 0.001), which were both lower in the NACT+surgery group. At estimated maintenance costs, p